Relationship between healthcare worker surface contacts, care type and hand hygiene: an observational study in a single-bed hospital ward. Issue 1 (September 2016) - King, M-F.; Noakes, C.J.; Sleigh, P.A.; Bale, S.; Waters, L.
Summary: This study quantifies the relationship between hand hygiene and the frequency with which healthcare workers (HCWs) touch surfaces in patient rooms. Surface contacts and hand hygiene were recorded in a single-bed UK hospital ward for six care types. Surface contacts often formed non-random patterns, but hygiene before or after patient contact depends significantly on care type ( P =0.001). The likelihood of hygiene correlated with the number of surface contacts (95% confidence interval 1.1–5.8, P =0.002), but not with time spent in the room. This highlights that a potential subconscious need for hand hygiene may have developed in HCWs, which may support and help focus future hygiene education programmes.